The changing nature of performance : implications for staffing, motivation, and development - Ilgen, Daniel R.; Pulakos, Elaine Diane (San Francisco : Jossey-Bass Publishers, 1999)
"Despite the major impact changes in systems, strategies, and organizational structures have had on the way we do business, the performance of individual employees remains the most important factor determining a company's success. But the task of evaluating and affecting performance is more of a challenge today than ever before. In this book, two dozen experts help human resource professionals meet that challenge by identifying the business trends that have had the biggest effect on employee performance and by providing specific strategies that will increase their ability to measure and manage it."--Jacket.
Introduction : Employee performance in today's organizations / Daniel R. Ilgen, Elaine D. Pulakos -- pt. 1. Changes in work that impact performance. Technology and performance / Beryl Hesketh, Andrew Neal -- Performance assessment in unique jobs / Stephan J. Motowidlo, Mark J. Schmit -- Contingent employees : individual and organizational considerations / Charles L. Hulin, Theresa M. Glomb -- Continuous learning / Manuel London, Edward M. Mone -- Customer-driven employee performance / David E. Bowen, David A. Waldman -- Leadership and the changing nature of performance / Robert G. Lord, Wendy Gradwohl Smith -- Developing adaptive teams : a theory of compilation and performance across levels and time / Steve W.J. Kozlowski [and others] -- pt. 2. The effect of change on three key processes-- staffing, motivation, and employee development. The challenge of staffing a postindustrial workplace / Kevin R. Murphy -- Managing work role performance : challenges for twenty-first-century organizations and their employees / Patrice R. Murphy, Susan E. Jackson -- Performance and employee development / Kurt Kraiger -- pt. 3. Concluding remarks. The definition and measurement of performance in the New Age / John P. Campbell.
Includes bibliographical references and indexes.
Keywords: Performance standards; Personnel management; Work environment; Employee Performance Appraisal; Personnel Management; Task Performance and Analysis; Workplace; Personnel -- Evaluation; Personnel -- Direction; workplace; Work environment; Personnel management; Performance standards; Personalpolitik; Performance standards